Mononuclear Phagocyte Activation Is Associated With the Immunopathology of Psoriasis - Costa, Mariana C.; Paixão, Camilla S.; Viana, Débora L.; Rocha, Bruno de O.; Saldanha, Maíra; da Mota, Lícia M. H.; Machado, Paulo R. L.; Pagliari, Carla; de Oliveira, Maria de Fátima; Arruda, Sergio; Carvalho, Edgar M.; Carvalho, Lucas P. (Frontiers in Immunology, 2020)
Psoriasis is a chronic, inflammatory disease affecting the skin and joints. The pathogenesis of this disease is associated with genetic, environmental and immunological factors, especially unbalanced T cell activation and improper keratinocyte differentiation. Psoriatic lesion infiltrate is composed of monocytes and T cells, and most studies have focused on the participation of T cells in the pathogenesis of this disease. Here we investigated the contribution of mononuclear phagocytes in the immunopathology observed in psoriatic patients. Significant increases in the levels of TNF, IL-1β, CXCL9, as well as the soluble forms of CD14 and CD163, were observed within the lesions of psoriatic patients compared to skin biopsies obtained from healthy individuals. Moreover, we found an association between the levels of CCL2, a monocyte attractant chemokine, and disease severity. In conclusion, our findings suggest a potential role for mononuclear phagocytes in the pathogenesis of psoriasis.